2010
DOI: 10.1161/hypertensionaha.110.151787
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Affects Renal-Adrenal and Hemodynamic Responses During Prolonged Standing in the Postural Orthostatic Tachycardia Syndrome

Abstract: Abstract-Approximately 500 000 American premenopausal women have the postural orthostatic tachycardia syndrome (POTS). We tested the hypothesis that in POTS women during orthostasis, activation of the renin-angiotensin-aldosterone system is greater, leading to better compensated hemodynamics in the midluteal phase (MLP) than in the early follicular phase of the menstrual cycle. Ten POTS women and 11 healthy women (controls) consumed a constant diet 3 days before testing. Hemodynamics and renal-adrenal hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 49 publications
2
50
1
Order By: Relevance
“…Previous work from our laboratory has demonstrated that a smaller and less “distensible” heart in young women or in healthy individuals after bed rest deconditioning can result in a larger reduction in stroke volume during orthostasis as a function of the Frank-Starling mechanism, leading to an excessive increase in HR (50). Consistent with our previous preliminary observations reported in abstract format (51), upright stroke volume was markedly smaller in POTS patients than healthy controls in this study. The orthostatic tachycardia observed in these patients thus appeared to be a physiological compensatory response to the smaller stroke volume (51,52), which was attributable to cardiac atrophy and reduced blood volume.…”
Section: Discussionsupporting
confidence: 93%
“…Previous work from our laboratory has demonstrated that a smaller and less “distensible” heart in young women or in healthy individuals after bed rest deconditioning can result in a larger reduction in stroke volume during orthostasis as a function of the Frank-Starling mechanism, leading to an excessive increase in HR (50). Consistent with our previous preliminary observations reported in abstract format (51), upright stroke volume was markedly smaller in POTS patients than healthy controls in this study. The orthostatic tachycardia observed in these patients thus appeared to be a physiological compensatory response to the smaller stroke volume (51,52), which was attributable to cardiac atrophy and reduced blood volume.…”
Section: Discussionsupporting
confidence: 93%
“…Also, we did not control for the phase of the menstrual cycle in which patients were evaluated. However, in a previous study, the menstrual cycle did not affect orthostatic HR responses, BV or PRA at 30 min on standing in POTS women [35]. Finally, a relatively small number of non-CFS–POTS patients were included in the BV assessments that may have introduced a type II error (false negative results).…”
Section: Discussionmentioning
confidence: 98%
“…The phase of the menstrual cycle can exert important effects on NO-dependent mechanisms. There is also evidence indicating differences in renin activity and serum aldosterone but not in CO, stroke volume, blood pressure, heart rate, or total peripheral resistance in the midluteal phase compared with the early follicular phase of the menstrual cycle in POTS (5).…”
Section: Limitationsmentioning
confidence: 99%